Ophthalmic drug-loaded N,O-carboxymethyl chitosan hydrogels: synthesis, in vitro and in vivo evaluation - Yang Li-qun; Lan Yu-qing; Guo Hui; Cheng Liang-zheng; Fan Ji-zhou; Cai Xiang; Zhang Li-ming; Chen Ru-fu; Zhou Huai-sheng (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the ability of drug-loaded N,O-carboxymethyl chitosan (CMCS) hydrogels to modulate wound healing after glaucoma filtration surgery. Methods: The drug-loaded CMCS hydrogels were in situ synthesized using genipin as the crosslinker in the presence of 5-fluorouracil (5FU) or bevacizumab. Their structures were characterized by FTIR, ultraviolet-visible (UV-vis) spectroscopy and scanning electron microscopy (SEM). In-vitro drug release experiments and in vivo evaluation in rabbits were performed. Results: The results of FTIR, UV-vis spectroscopy and SEM analyses indicated that 5FU was encapsulated into the CMCS hydrogels that were crosslinked by genipin. The in vitro drug release experiments showed that nearly 100% of 5FU was released from the drug-loaded hydrogels within 8 h, but less than 20% bevacizumab was released after 53 h. The in vivo evaluation in rabbits indicated that the drug-loaded CMCS hydrogels were nontoxic to the cornea and were gradually biodegraded in the eyes. Furthermore, the drug-loaded CMCS hydrogels effectively inhibited conjunctival scarring after glaucoma filtration surgery and controlled postoperative intraocular pressure (IOP). Conclusion: The drug-loaded CMCS hydrogels provide a great opportunity to increase the therapeutic efficacy of glaucoma filtration surgery.